Phytoremediation of calcareous saline-sodic soils with mesquite (Prosopis glandulosa). (19th May 2017) - Abdalla, Mubarak Abdelrahman; Awad Elkarim, Abdelkarim Hassan; Taniguchi, Takeshi; Endo, Tsuneyoshi; Yamanaka, Norikazu
ABSTRACT: We evaluated phytoremediation potential of a calcareous saline-sodic soil with Prosopis glandulosa relying on either N2 fixation (NFIX) or inorganic N (IN) and gypsum. Straw and root dry matter of NFIX were 60% and 67% higher than that of IN, respectively. While both plants relying on IN or NFIX retained nearly similar Ca 2+, Na + level in IN lysimeters was 1.8 folds that of NFIX, whereas levels of Na + and K + in roots of NFIX were 13% and 24% higher than that of IN plants. P. glandulosa relying on NFIX and IN released 39% and 50% Na + of that released by the gypsum. P. glandulosa produced more than the gypsum treatment and induced 24% of Ca 2+ solubilization found in the gypsum treatment. Translocation factor of Na + and the K + /Na + ratio in NFIX and IN were 0.58, 0.99 and 13.2, 7.0, respectively. The practical implication of this study conclude that P. glandulosa grown with NFIX or IN is an alternative practice for amelioration of calcareous salt-affected soils.